NEW SIMILARITY MEASURES OF INTERVAL VALUED FUZZY SOFT SET AND ITS APPLICATION - Rajarajeswari, Dr. P (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper, we proposed the concept of reduced fuzzy soft set of interval valued fuzzy soft set and also defined different types of reduction along with it. Then based on these reduction, three types of similarity measures are done with example .Also we developed an algorithm which is a new approach in the medical diagnosis field by employing reduced fuzzy soft set of interval valued fuzzy soft set. Keywords: Soft set, fuzzy soft set, interval valued fuzzy soft set, reduced fuzzy soft set.